Extracellular Matrix Applications in the Treatment of Open Fractures With Complex Wounds and Large Soft Tissue Defects. Issue 2 (February 2018) - Fokin, Alexander A.; Puente, Ivan; Hus, Nir; Rodriguez, Eugenio; Weisz, Russell D.
Abstract : Summary: Use of biologic scaffolds such as extracellular matrix (ECM) is a promising trend in the treatment of complex wounds in orthopedic trauma patients. In this clinical series we describe the technique of the successful application of porcine urinary bladder ECM products in the treatment of open fractures of the extremities with complex wounds and large soft tissue defects. The clinical outcomes demonstrated that even in challenging cases where local flap coverage of bone or neurovascular structures is not possible, sequential xenograft implantation allowed us to achieve a stable soft tissue envelope. Different forms of ECM products are easy to apply in the presence of orthopedic hardware. In certain wounds, complete closure can be achieved even without subsequent skin grafting. We recommend relatively earlier application of xenograft.